Cost of Hemodialysis Treatment and Associated Factors Among End-Stage Renal Disease Patients at the Tertiary Hospitals of Addis Ababa City and Amhara Region, Ethiopia - Kassa DA; Mekonnen S; Kebede A; Haile TG (Dove Medical Press, 2020)
Daniel Asrat Kassa,1 Solomon Mekonnen,2 Adane Kebede,1 Tsegaye Gebremedhin Haile1 1Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Human Nutrition, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tsegaye Gebremedhin HaileDepartment of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, PO Box 196, Gondar, EthiopiaTel +251-921279362Email tsegishg27@gmail.comPurpose: Hemodialysis is a renal replacement therapy for end-stage renal disease (ESRD) patients who consume substantial healthcare resources, which increases the economic burden. Plenty of factors affects the cost of hemodialysis treatment, particularly in resource-limited settings. Moreover, the demand for hemodialysis may decrease as the cost increases, but there is limited evidence in Ethiopia. Thus, this study aimed to estimate the cost of hemodialysis treatment among ESRD patients in the tertiary hospitals of Addis Ababa City and Amhara region, Ethiopia.Patients and Methods: An institutional-based cross-sectional study was conducted among 172 ESRD patients undergoing hemodialysis treatment. A structured questionnaire and patients’ medical chart were used to estimate the costs, and the human capital approach was applied to calculate the indirect costs. A generalized linear model (GLM) was fitted after the modified park test to identify the associated factors. In the final GLM, a p-value of < 0.05 and a 95% CI were used to declare the significant variables.Results: The mean annual cost of hemodialysis treatment was 121,089.27ETB ($4466.59) ± 33,244.99 ($1226.29). The direct and indirect costs covered 77.0% and 23.0% of the total costs, respectively. Age (ex(b): 1.01, p-value < 0.001), highest wealth status (ex(b): 1.09, p-value: 0.008), eight (ex(b): 1.27, p-value < 0.001) and 12 visits/month (ex(b): 1.34, p-value < 0.001), anemia (ex(b): 1.13, p-value < 0.001), and comorbidity (ex(b): 1.09, p-value: 0.039) were the factors associated with the costs of hemodialysis treatment.Conclusion: The annual cost of hemodialysis treatment among ESRD patients was high compared to the national per capita health expenditure, and two-thirds covered by the direct medical costs. Old age, high wealth status, more visits, anemia, and comorbidity were factors associated with the costs of hemodialysis. Therefore, the healthcare system must make a great effort for cost reduction and reduce the patients with kidney disease before they reach end-stages.Keywords: burden of ESRD, direct costs, indirect costs, GLM, hemodialysis, Ethiopia